Thirty-year Perspective of the Long-term Survival, CD4 Percentage and Social Achievements of Perinatally HIV-infected Children as a Function of Their Birth Era. Issue 2 (February 2017) - Vuppula, Sharon; Tyungu, Donna; Kaul, Aditya; Chandwani, Sulachni; Rigaud, Mona; Borkowsky, William
Abstract : Background: Pediatric HIV has evolved from a pre-antiretroviral (ART) era (pre-1989 or pre-ART) to an ART era (1989 to 1996) and to a highly active antiretroviral therapy (HAART) era (post-1996). As we have passed the third decade following these individuals, we thought it useful to review clinical, laboratory and social outcomes. Methods: A retrospective, cross-sectional study of 399 children infected perinatally. They were divided into pre-ART, ART and HAART groups. A Kaplan-Meier plot was constructed. One hundred seventy-nine have been lost to follow-up at an average of 7.6 (0.3–27.6) years. Results: Approximately 40%, 80% and 90% of individuals in the pre-ART, ART and HAART groups have long-term survival. One hundred twenty-one died at an average of 5.1 (0–26.1) years. Pre-ART, ART and HAART groups had mean most recent CD4% values (±SEM) of 16.74 (1.09), 22.97 (0.96) and 33.07 (2.09), respectively ( P < 0.001). Pre-ART RNA is limited in that era and present if they survived to another era. In this group, the median RNA values in those who died (311, 300, n = 16) was greater than in survivors (19, 402, n = 45). Forty-three percent of the individuals in the ART group and 77% of individuals in the HAART group had most recent HIV RNA <400 copies/mL. Eighteen individuals >18 years of age have only a grade school or no education. Fifty-five have graduated high school or received an equivalency diploma. Twenty-three more have completed college. Nadir and recent CD4% of those who did and did not complete high school was equivalent to college graduates. Sixteen survivors (1/2 male) have had 18 uninfected children. Conclusions: This first long-term follow-up study demonstrates remarkable survival and social skills of our patients.